Machine Tools for High Performance Machining - Norberto (Springer, 2012)
Machine tools are the main production factor for many industrial applications in many important sectors. Recent developments in new motion devices and numerical control have lead to considerable technological improvements in machine tools. The use of five-axis machining centers has also spread, resulting in reductions in set-up and lead times. As a consequence, feed rates, cutting speed and chip section increased, whilst accuracy and precision have improved as well. Additionally, new cutting tools have been developed, combining tough substrates, optimal geometries and wear resistant coatings. “Machine Tools for High Performance Machining” describes in depth several aspects of machine structures, machine elements and control, and application. The basics, models and functions of each aspect are explained by experts from both academia and industry. Postgraduates, researchers and end users will all find this book an essential reference.